Conceptual Metaphor Analysis on Terrorism in Indonesian Online Mass Media - Anandya Asprillia (Universitas Brawijaya, 2023)
Since the existence of the Conceptual Metaphor Theory by Lakoff and Johnson (2003), many research has focused on how the conceptualization of the abstract domain is represented in a concrete domain. This leads to a realization that metaphor is more than just a poetic device, it can show how a community understands an abstract concept using a more concrete one. In this study, conceptual metaphors of terrorism are investigated to find out how the Indonesian mass media represent it in their publication. The results show that most of the metaphors are conceptually related to LIVING ORGANISM while one being specific to Indonesian culture, which is SHADOW PUPPET. In contrast, there are no violent conceptual metaphors found in the Indonesian mass media, such as TERRORISM IS WAR or DISEASE. This can bring different effects on the readers of mass media, such as psychological and social. Also understanding the conceptual metaphors in mass media can help us understanding the framing of terrorism, in this case, in Indonesia.